Ultrasound imaging of the fetal secondary palate: Methodological description of a two‐dimensional approach and a case series. (16th December 2018) - Brusilov, Michael; Wolman, Igal; Ashwal, Eran; Malinger, Gustavo; Birnbaum, Roee
Abstract: Objective: The study aims to describe our two‐dimensional (2D) ultrasound approach to visualize the fetal secondary palate and plot its growth curve and to describe and demonstrate its clinical implementation. Methods: This is a two parts retrospective study. First, we measured the antero‐posterior length of the bony secondary palate, from the soft to hard palate interface (SHPI) line to the alveolar ridge, blindly by two operators during routine scans of low‐risk fetuses, and plot a longitudinal growth curve. In the second part, we describe four cases of prenatal diagnosis of secondary palate cleft. Results: Sixty‐eight fetuses were included: 14 to 15 weeks (n = 20), 21 to 24 weeks (n = 32), and 29 to 35 weeks (n = 16). The bony secondary palate elongates along gestation from a mean of 5.3 mm (+/−0.46 mm) at 14 to 15 weeks to 15.9 mm (+/−1.7 mm) at 29 to 35 weeks. We found high intraobserver and interobserver correlation between measurements. All four cases diagnosed by this approach were confirmed postnatally. Conclusions: The SHPI, representing the normally developed secondary bony palate, can be imaged in the fetus by direct 2D ultrasound as early as 14 weeks. A gap within or nonvisualization of the SHPI is highly suggestive for a secondary palate cleft. Abstract : What's already known about this topic? Prenatal detection rates of cleft lip and palate are variable. Isolated clefts of the secondary palate are missed prenatally in the majority of cases. Two‐dimensional (2D) ultrasound (US) imaging of the secondary palate has been described in a limited number of publications. What does this study add? We provide here additional data showing that the posterior aspect of the bony secondary palate can be readily imaged by direct 2D US by following the suggested steps. Gaps within or nonvisualization of this structure is highly suggestive of a secondary palate cleft, which can be diagnosed during routine scans by 2D US.